Collateral Spread and Financial Development - LIBERTI, JOSÉ M.; MIAN, ATIF R. (Journal of Finance, 2010)
ABSTRACT We show that institutions that promote financial development ease borrowing constraints by lowering the collateral spread and shifting the composition of acceptable collateral towards firm‐specific assets. Collateral spread is defined as the difference in collateralization rates between high‐ and low‐risk borrowers. The average collateral spread is large but declines rapidly with improvements in financial development driven by stronger institutions. We also show that the composition of collateralizable assets shifts towards non‐specific assets (e.g., land) with borrower risk. However, the shift is considerably smaller in developed financial markets, enabling risky borrowers to use a larger variety of assets as collateral.